Constructing Gender-Sensitive Culture through Language Learning - Suciati, Sri; Umaya, Nazla Maharani (Jurnal Pendidikan Indonesia, 2025)
Gender stereotypes still exist in the educational process. This can be seen from the biased attitudes of teachers towards their students and biased texts in school textbooks, both in the form of sentences and images. One way to overcome this is through Indonesian language lessons. The purpose of this study is to analyze efforts that can be made to build a gender-sensitive culture through language learning. This study used a quantitative survey method. The research respondents comprised 185 junior high school teachers of Indonesian language subjects selected using a purposive sampling technique. Data were collected through a Google Form, containing a closed questionnaire. Data analysis was carried out using SPSS. The results showed that the majority of teachers showed a supportive attitude towards efforts to build a gender-sensitive culture through language learning, which includes: a) the implementation of gender-equal character education through Indonesian language lessons; b) the use of gender-neutral materials in Indonesian language lessons; and c) the application of gender-sensitive pedagogy. A gender-sensitive culture can be built through language learning. This research implies that teachers can use it as a guide in educating students about gender equality, textbook compilers to use language that upholds gender equality in compiling books, and the government as curriculum and policy makers to implement gender equality in education fairly and evenly.